Pentingnya Sertifikasi Halal Bagi Para Pelaku UMKM untuk Meningkatkan Nilai Jual Ekonomi di Desa Rejosari - Muhammad Faza Akbar; Ahmad Faiq Khariri; Alfina Gusmiarni; Naifah Nur Laila; Nikmah Rina Wulandari; Rita Ariyana Nur Khasanah (Lembaga Pengembangan Kinerja Dosen, 2024)
Halal certification plays a crucial role in ensuring that a product is safe for consumption and complies with Islamic principles. Additionally, halal certification can also enhance a product's competitiveness. This study aims to provide understanding and knowledge to the community, particularly to Micro, Small, and Medium Enterprises (MSMEs), about the importance of halal certification for a product in supporting sales growth, especially for food products. Using a qualitative approach, interviews and observations were conducted with MSME operators. The research findings indicate that limited access to information and low public awareness about halal certification are major barriers to implementing halal certification in the village. In this context, the government has appointed the Halal Product Assurance Agency (BPJPH) of the Ministry of Religious Affairs (Kemenag) of the Republic of Indonesia to intensify halal certification for food industry producers. The requirements and procedures for obtaining halal certification need to be socialized to the broader community, particularly MSME operators. Thus, the KKN Team of UIN Walisongo, together with BPJPH, aims to assist the government program by providing information and understanding to the Rejosari village community about the importance of holding a halal certificate, which can help enhance the economic value of the village.